2014
DOI: 10.1186/1756-3305-7-184
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of larvicidal activity of the essential oil of Allium macrostemon Bunge and its selected major constituent compounds against Aedes albopictus (Diptera: Culicidae)

Abstract: BackgroundDuring the screening programme for new agrochemicals from Chinese medicinal herbs and local wild plants, the essential oil of dried bulbs of Allium macrostemon Bunge (Liliaceae) was found to possess larvicidal activity against mosquitoes. The aim of this research was to determine the larvicidal activity of the essential oil and its major constituent compounds against the larvae of the Culicidae mosquito, Aedes albopictus.MethodsEssential oil of A. macrostemon was obtained by hydrodistillation and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…However, compared with the other essential oils using the same bioassay in the literature, essential oil of I. henryi leaves exhibited the same level or stronger larvicidal activity against A. albopictus larvae, e.g. essential oils of Foeniculum vulgare fruits (LC 50 = 142.9 μg/ml) [18], Eucalyptus urophylla leaves (LC 50 = 95.5 μg/ml) [19], Allium macrostemon bulbs (LC 50 = 72.86 μg/ml) [6], Toddalia asiatica roots (LC 50 = 69.09 μg/ml) [5], Zanthoxylum avicennae leaves (LC 50 = 48.79 μg/ml) [7], aerial parts of Salvia elegans and S. splendens (LC 50 = 46.4 ppm and LC 50 = 59.2 ppm, respectively) [20] and Clinopodium gracile aerial parts (42.56 μg/ml) [4].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, compared with the other essential oils using the same bioassay in the literature, essential oil of I. henryi leaves exhibited the same level or stronger larvicidal activity against A. albopictus larvae, e.g. essential oils of Foeniculum vulgare fruits (LC 50 = 142.9 μg/ml) [18], Eucalyptus urophylla leaves (LC 50 = 95.5 μg/ml) [19], Allium macrostemon bulbs (LC 50 = 72.86 μg/ml) [6], Toddalia asiatica roots (LC 50 = 69.09 μg/ml) [5], Zanthoxylum avicennae leaves (LC 50 = 48.79 μg/ml) [7], aerial parts of Salvia elegans and S. splendens (LC 50 = 46.4 ppm and LC 50 = 59.2 ppm, respectively) [20] and Clinopodium gracile aerial parts (42.56 μg/ml) [4].…”
Section: Discussionmentioning
confidence: 74%
“…Fortunately, essential oils and their constituents have been suggested as alternative sources for insect control. Many studies have demonstrated that essential oils and their individual components possess promising larvicidal activities against mosquito vectors [3][4][5][6][7][8]. During our mass screening program for new agrochemicals from the wild plants, essential oil of Illicium henryi Diels leaves (Family: Illiciaceae) was found to possess larvicidal activity against the Asian tiger mosquito, A. albopictus Skuse.…”
Section: Introductionmentioning
confidence: 99%
“…One study revealed that the essential oil of Allium macrostemon bulbs and its two major constituents demonstrate strong larvicidal activity against Aedes albopictus mosquito larvae. The results suggested that the essential oil of A. macrostemon and the two major constituents may be recommended effectively in mosquito control, they also suggested further evaluation for safety in humans and to enhance their activity [30]. Rajkumar and Jebanesan, analysed essential oil obtained by steam distillation of leaves of Clausena dentata.…”
Section: Mode Of Action Of Essential Oilsmentioning
confidence: 99%
“…However, repeated and injudicious application of these synthetic insecticides have caused disrupt of the natural biological control systems and sometimes resulted in the widespread development of resistance as well as undesirable effects on non-target organisms, toxic residues in food, workers' safety, and high cost of procurement [4]. Essential oils and their constituents have been suggested as alternative sources for conventional mosquito larvicides [5][6][7]. During the present author's mass screening program for new agrochemicals from wild plants and Chinese medicinal herbs, the essential oil of Dipsacus asper Wallich ex Candolle (Family: Dipsacaceae) roots, was found to possess larvicidal activity against the larvae of A. aegypti and C. pipiens pallens.…”
Section: Introductionmentioning
confidence: 99%